Energy Efficiency In Wireless Sensor Network Using Dynamic Duty Cycle Based Sensor Mac - et. al., Saravanakumar Pichumani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Wireless Sensor Network is created by a huge number of sensor nodes normally powered by batteries and may not easily recharged. To extend the lifetime of the sensor node is a vital issue while designing a protocol in WSN. However, lowering the energy consumption may result in higher latency. To address on such trade-off issues, this paper proposes Sensor MAC (SMAC) dynamic duty cycle to improve SMAC fixed duty-cycle. S-MAC adjusts the duty-cycle based on dynamic utilization and average sleep delay. The proposed topology which is distributive in nature, controls the technique to schedule the nodes to wakeup time slots, and design a SMAC protocol to get benefitted from this topology control for improving the energy-efficiency, delay, and efficiently handling the spatially-correlated contention. Compared to Fixed SMAC the Dynamic SMAC lowers the Energy consumption in Fixed SMAC and performs very good Energy saving in circular, grid and random topologies.